2011
DOI: 10.1080/15378020.2011.625824
|View full text |Cite
|
Sign up to set email alerts
|

Why Restaurants Fail? Part II - The Impact of Affiliation, Location, and Size on Restaurant Failures: Results from a Survival Analysis

Abstract: It has been suggested that changes in organizational populations are shaped by a natural (biological) selection process. Industries and businesses evolve through standard and identifiable phases throughout their lifespan. This study analyzed organizational mortality in the restaurant sector based on restaurant location, affiliation (presence/no presence of multi-unit locations of restaurants in a given geographical area), and size. Objectives of this study are to understand organizational failure from a popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 47 publications
10
62
0
4
Order By: Relevance
“…Most full-service restaurants tend to be larger in size and also offer lucrative alcohol service, whereas QSRs tend to be smaller in size with limited or no alcohol service. Our observation here that high restaurant failure can be attributed partially to the style of service is consistent with Parsa et al (2011). Another finding from this study that supports previous studies (International Franchise Association 2010; Khan 2014; Walker 2012) is that chain restaurants had lower failure rates (21.43%) compared with non-chain independent restaurants (33.33%).…”
Section: Zip Codesupporting
confidence: 91%
See 1 more Smart Citation
“…Most full-service restaurants tend to be larger in size and also offer lucrative alcohol service, whereas QSRs tend to be smaller in size with limited or no alcohol service. Our observation here that high restaurant failure can be attributed partially to the style of service is consistent with Parsa et al (2011). Another finding from this study that supports previous studies (International Franchise Association 2010; Khan 2014; Walker 2012) is that chain restaurants had lower failure rates (21.43%) compared with non-chain independent restaurants (33.33%).…”
Section: Zip Codesupporting
confidence: 91%
“…Thus, to overcome the limitations of the many definitions of success and failure, we have used the definition that was successfully used by earlier studies on this topic, where a business failure is defined as a change in business ownership of an existing business irrespective of the reasons behind the ownership turnover. This definition was adapted from the earlier studies on this topic by Watson and Everett (1996b), Parsa et al (2005), Parsa et al (2011), and other studies where business failure was defined as change in ownership as reported in local health department records. This countenances, for example, the situation of a restaurateur who is adept at starting a business, but may not be able to run the restaurant once it is launched.…”
Section: Definition Of Success and Failurementioning
confidence: 99%
“…Despite its economic benefit to the society, it has been documented that small restaurant businesses tend to lose customers as compared to other food related service providers like food vendors, take away food service providers, pubs, bars, and catering services (Parsa et al, 2011). As a result, small restaurant businesses performance and their survival remain questionable (Parsa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…External factors include the requirement for relatively low capital investment in small hospitality businesses, less dependency on specialist knowledge, and relatively low qualification barriers (Lockyer and Morrison, 1999), but this comparatively easy access to hospitality business ownership can cause problems for those lacking experience or business acumen. The importance of size, location, competitive density, and chain affiliation for restaurants is therefore acknowledged as influential on closures (Parsa et al, 2011), as are internal factors such as the owners' characteristics (Parsa et al, 2005) and stress (Wallace, 2003).…”
Section: Influences On Closuresmentioning
confidence: 99%
“…Although there is a wealth of research on successful (e.g. Walker andBrown, 2004, Camillo et al, 2008) and unsuccessful (Watson and Everett, 1996, Parsa et al, 2005, Parsa et al, 2011 entrepreneurship in the industry, some closures are not caused by bankruptcy or retirement, but by the owners' decisions to return to paid work (Watson and Everett, 1996). Little is known about these entrepreneurial 'drop-outs', who for unknown reasons, sell successful businesses and return to paid employment.…”
Section: Introductionmentioning
confidence: 99%